Pengaruh media pembelajaran diorama terhadap hasil belajar IPAS pada materi kegiatan ekonomi siswa SDN 69 Palembang - Amelia Citranatasya; Lukman hakim; Dina sri nindiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Diorama learning media is a visual aid in the form of a three-dimensional miniature that depicts a scene, event, or a certain concept in real terms to help the learning process to be more interesting, concrete, and easy to understand by students. The purpose of this study was to determine the effect of diorama learning media on the results of learning science in the material of economic activities at SDN 69 Palembang. The method used is this study uses an experimental research method (experimental research). In this study, the researcher used the Nonequivalent Control Group Design design. The subjects in this study were class IV.A and class IV.B totaling 46 students. Data collection was carried out using test and documentation techniques. The data analysis technique used test questions that were carried out using the Normality test, Homogeneity test, and hypothesis test. The results of the data analysis showed that the results of the hypothesis test, the t-count value was 3.042≥2.015 t table and the significance value was ≤ 0.025 (0.004≤0.025). So it can be concluded that there is an effect of diorama learning media on the results of learning science in the material of economic activities at SDN 69 Palembang. Keywords: Diorama learning media, Learning Outcomes, Science.